Exploring Types and Functions of Speech Acts in Anyone But You Movie (2023) - Yunia, Veny; Rofik, Abdur (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2024)
This study is aimed to analyze : (1) kinds of speech act are present in the dialogue film Anyone But You (2023), (2) what functions of speech act are present in the dialogue of the film Anyone But You (2023). This study examines the movie using a descriptive, qualitative approach entitled Anyone But You (2023) directed by Will Gluck as the objective research. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analyzing data of the research method by using displaying, explaining, and interpreting. The data is analyzed by the researcher using a pragmatic approach with Speech Act and Halliday’s Language Function theory. The result of the research : (1) all kinds of illocutionary speech act are present in the film Anyone But You (2023) such as declarative, representative, expressive, directive, and commissive; (2) language functions are present in the dialogue of the movie Anyone But You (2023) are in the form of seven language functions, that are regulatory function, instrumental function, representational function, interactional function, heuristic function, personal function, and imaginative function.